Comparative insect fauna succession on indoor and outdoor monkey carrions in a semi-forested area in Malaysia - Ahmad, N.W.; Lim, L.H.; Dhang, C.C.; Chin, H.C.; Abdullah, A.G.; Wan, W.N.; Mustaffa, C.W.K.; Jeffery, J.; Hashim, R.; Sofian-Azirun, Mohd (2011)
Objective To study the occurrence of insects fauna obtained in a semi forested area in Malaysia using the carcass of the monkey Macaca fascicularis, Raffles, and to compared the wave of insect succession collected from the carcass placed outdoor and indoor. Methods The outdoor and indoor studies were conducted at a location of 3Â°17â²57.86â³N, 101Â°47â²00.78â³E. The euthanized monkeys were placed indoor and outdor. The insect seccession visited the carcass, the envirenmental temperature and relative humidity were recorded. Results The main insects attracted to specific stages of decomposition were mainly members of Diptera and Coleoptera. There was a delay of fly arrival by two days in indoor carcass. Nocturnal oviposition behaviour was not observed in this study. The flies left the carcass during the twilight zone as noted during a 3 days observation period in outdoor study. The dipteran species found outdoor and indoor were similar but more diverse coleopteran species was found indoor. Conclusions Information and evidence from this study can be used to improve the estimation of the post mortem interval in forensic cases.